2020
DOI: 10.1134/s2079978020010033
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Iodophors: Preparation, Properties, and Biomedical Applications

Abstract: The review summarizes the data on the main chemical and physiological properties of iodine and its capability of complexation with natural and synthetic polymers. Iodine is the best known antiseptic used to prevent and treat microbial infections. Its unique capability of complexation with certain polymers opens wide opportunities for targeted and prolonged delivery to target organs. Polymeric complexes with iodine have another color, other morphology, a higher electrical conductivity, and higher biological act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 101 publications
0
34
0
4
Order By: Relevance
“…These disadvantages can be controlled by stabilizing the iodine structure. Iodine can form polyiodides through attachment of iodide anions (I − ), triiodide ions (I 3 − ) and iodine molecules (I 2 ) as the basic units [47,49,50]. The polyiodides can vary from isolated to two-and three-dimensional networks with polymeric structure [47,[49][50][51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These disadvantages can be controlled by stabilizing the iodine structure. Iodine can form polyiodides through attachment of iodide anions (I − ), triiodide ions (I 3 − ) and iodine molecules (I 2 ) as the basic units [47,49,50]. The polyiodides can vary from isolated to two-and three-dimensional networks with polymeric structure [47,[49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Iodine can form polyiodides through attachment of iodide anions (I − ), triiodide ions (I 3 − ) and iodine molecules (I 2 ) as the basic units [47,49,50]. The polyiodides can vary from isolated to two-and three-dimensional networks with polymeric structure [47,[49][50][51]. Polyiodides contain different patterns of bonding, including halogen bonding [47,[52][53][54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%
“…It is composed of iodine binding to polyvinylpyrrolidone and is soluble in water. [233,234] PI is an active antiseptic reagent against gramnegative and gram-positive bacteria, fungi, protozoa, and several viruses such as the H1N1 flu virus. [235][236][237] Based on previous reports, PI (10%) is considered as a first antiseptic for treatment of superficial skin infections, and it promotes wound healing.…”
Section: Antiseptic Reagentsmentioning
confidence: 99%
“…PVP-I was introduced as an antiseptic by Shelanski and Shelanski in 1956 [39]. It is formed by joining iodine molecules with polyvinylpyrrolidone and is water-soluble [5]. In PVP-I, povidone acts as an iodine carrier and is capable of absorbing iodine and transporting it, but does not react with the iodine.…”
Section: Povidone-iodine (Polyvinylpyrrolidone-iodine; Pvp-iodine)mentioning
confidence: 99%
“…Doctors did not use gloves and washed their hands after surgery rather than before. Post-operative mortality at that time reached 75% [5]. Ignaz Semmelweis observed that the maternity ward in which doctors and students worked had a mortality rate of 20%, while the maternity ward in which midwives worked had a mortality rate of only 3%.…”
Section: Introductionmentioning
confidence: 99%